Reading and Deafness: State of the Evidence and Implications for Research and Practice - Beverly Trezek; Connie Mayer (MDPI AG, 2019)
Over the years, persistently low achievement levels have led scholars to question whether reading skill development is different for deaf readers. Research findings suggest that in order for deaf students to become proficient readers, they must master the same fundamental abilities that are well established for hearing learners, regardless of the degree of hearing loss or communication modality used (e.g., spoken or signed). The simple view of reading (SVR), which hypothesizes the critical role both language abilities and phonological skills play in development of reading comprehension, provides a model for understanding the reading process for a wide range of students and has the potential to shed light on the challenges deaf students have historically experienced in achieving age-appropriate outcomes. Therefore, the purpose of this paper is to review the components of the SVR and use this conceptual model as the basis for exploring and discussing both historical and current research evidence in reading and deafness, with a particular focus on phonological skills. Recommendations for future research and practice based on the existing body of literature will also be provided.